2022
DOI: 10.47278/journal.ijvs/2022.200
|View full text |Cite
|
Sign up to set email alerts
|

Using in-ovo injection of olive pulp extract and vitamin C to improve hatchability, post hatch growth performance, carcass traits and some biochemical blood analysis in broiler chickens

Abstract: A total of 630 fresh hatching eggs containing live embryo at 14 day of incubation were distributed randomly into seven treatment groups (three replicates/treatment, 30eggs/each) and the fertile eggs were injected in the yolk sac as following groups: eggs were un –injected (T1), eggs were injected with hole only as negative control (T2), eggs were injected with distilled water as positive control (T3), eggs were injected with OPE at 500 and 1000ppm/egg, T4 and T5), while eggs were injected with Vit C at 4 and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 26 publications
0
4
0
Order By: Relevance
“…An absent information on the direct influence of IO of EG and OL extracts was documented, although their dietary effect was illustrated in literature. Inconsistent result was obtained recently by Khalifa et al (2023), that IO into YS at 14 days of incubation with 1000 ppm olive pulp extract did not change hatchability and BW whereas the dose of 500 ppm decreased the hatchability.…”
Section: Hatchability and Chicks Parametersmentioning
confidence: 56%
See 3 more Smart Citations
“…An absent information on the direct influence of IO of EG and OL extracts was documented, although their dietary effect was illustrated in literature. Inconsistent result was obtained recently by Khalifa et al (2023), that IO into YS at 14 days of incubation with 1000 ppm olive pulp extract did not change hatchability and BW whereas the dose of 500 ppm decreased the hatchability.…”
Section: Hatchability and Chicks Parametersmentioning
confidence: 56%
“…Both T3 and T4 are produced under control of TSH and are important in regulating metabolism, muscular growth, heat production, eggshell pipping during hatching and mobilization of glycogen and fat stores (Givisiez et al, 2020). Comparable results indicated that levels of T4 along with T3 in blood were enhanced in hatched chicks by IO of 1000 mg olive pulp extract (Khalifa et al, 2023) or 30 mg naringin (Ranjbar et al, 2019). Opposite data to us, it was confirmed that high amount of serum T3 in hatched chicks was registered by IO into AC site at 17.5 days of heat-stressed embryos with 6 mg of black cumin (Oke et al, 2021) or with 2 mg of clove (Akosile et al, 2023b).…”
Section: H/l Ratio and Hormonal Responsementioning
confidence: 63%
See 2 more Smart Citations